Developing Arabic Language Instructional Materials for Mathematic Students in Islamic Higher Education in Indonesia - Kartini Kartini; Muhammad Ihsan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
The lack of relevance between Arabic language learning materials and students' academic disciplines has contributed to low engagement and language proficiency. This study aims to develop Arabic teaching materials integrated with mathematical content to enhance students' linguistic competence and mathematical reasoning. The research employs a Research and Development (R&D) approach, adopting the Hannafin and Peck model, which consists of three main stages: needs analysis, design, and iterative evaluation-based development. Participants included 72 students and 2 lecturers, with additional validation from 3 subject matter experts. Data were collected through needs analysis questionnaires, expert validation sheets, and practicality questionnaires. The findings reveal that: (1) 72.3% of students expressed a need for Arabic materials incorporating mathematical content; (2) Four core topics were identified for material development: numbers, fractions, geometry, and statistics; (3) Expert validation yielded scores >0.5 (valid category); and (4) The practicality level of the materials reached 81,3% (practical criteria). These results indicate that the developed interdisciplinary teaching materials not only meet validity and practicality standards but also have the potential to bridge students' academic and linguistic needs. The study recommends further effectiveness testing across various Islamic higher education contexts to strengthen the generalizability of the findings.